Modified atmosphere packaging of a traditional Malaysian nyonya cake: A preliminary study. - C., C. SEOW (1995)
Nyonya kuih comprises a group of popular traditional Malaysian "cakes" made principally from rice (waxy and non-waxy), tapioca, and sago flours or starches. They normally have a shelf-life from 1-3 days at· ambient storage temperatures (250 -300 e), depending on whether or not chemical preservatives are incorporated.